2019
DOI: 10.1038/s41598-019-48540-3
|View full text |Cite|
|
Sign up to set email alerts
|

Statin treatment after acute coronary syndrome: Adherence and reasons for non-adherence in a randomized controlled intervention trial

Abstract: Studies of secondary prevention for cardiovascular disease show low fulfilment of guideline-recommended targets. This study explored whether nurse-led follow-up could increase adherence to statins over time and reasons for discontinuation. All patients admitted for acute coronary syndrome at Östersund hospital between 2010–2014 were screened for the randomized controlled NAILED-ACS trial. The trial comprises two groups, one with nurse-led annual follow-up and medical titration by telephone to reach set interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
(40 reference statements)
2
9
0
1
Order By: Relevance
“…Analysis of adherence to lipid-lowering medication in this subgroup showed that discontinuation at some point during follow-up was common in both treatment groups, and that adverse symptoms with a non-compelling relationship to treatment was the dominating cause. In the control group, this was also the most common reason for permanent discontinuation 31 .…”
Section: Discussionmentioning
confidence: 95%
“…Analysis of adherence to lipid-lowering medication in this subgroup showed that discontinuation at some point during follow-up was common in both treatment groups, and that adverse symptoms with a non-compelling relationship to treatment was the dominating cause. In the control group, this was also the most common reason for permanent discontinuation 31 .…”
Section: Discussionmentioning
confidence: 95%
“…21 Multiple factors are thought to underpin this unmet treatment need, with suboptimal dosing, high rates of treatment discontinuation, and low rates of lipid-lowering therapy (LLT) adherence commonly observed. [22][23][24][25][26][27] Evolocumab is a PCSK9 inhibitor antibody approved to reduce the risk of MI, stroke, and coronary revascularization in adults with established CVD. 28 The efficacy of evolocumab is well established from clinical trials, with significant lowering of LDL-C and reduction of major CV events.…”
Section: Introductionmentioning
confidence: 99%
“…12,29 However, there are limited data on LDL-C lowering with evolocumab in real-world healthcare settings, where patient-, physician-, and payer-related treatment hurdles are common. 17,[22][23][24][25][26][27][30][31][32][33] Historically, these hurdles have included treatment discontinuation, educational needs for providers, prior authorization requirements, costs, and formulary restrictions. [30][31][32][33] In the current study, we characterized the population and assessed LDL-C lowering during 1 year of evolocumab therapy in realworld patients with LDL-C ≥ 70 mg/dL (≥ 1.8 mmol/L), including a patient subgroup with elevated risk hospitalized for MI within 12 months prior to starting evolocumab.…”
Section: Introductionmentioning
confidence: 99%
“…This intervention was found effective for LDL-C at the one-year follow-up [ 76 ], and after a mean 3.9 years of follow-up intervention group patients had mean LDL-C 2.0 mmol/L compared to 2.4 mmol/L in the control group. Patients in the intervention group were also more likely to stay on statin treatment, even though they also had a more intensive regimen [ 77 ]. The authors conclude that the continual patient-centered follow-up enables a joint trust and understanding of symptoms and causes, which can help prevent discontinuation of statin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This increases the need for pharmaceutical care and individualized follow-up assessing both clinical outcomes and the patient’s medication experience [ 91 ]. A continual patient-centered follow-up enables a joint trust and understanding of symptoms and causes, which can help prevent discontinuation of treatment [ 77 ]. Our study shows that including clinical pharmacists trained in motivational interviewing is one option to deliver support for patients in their management of medicines; and when this is based on patients’ individual needs, they commonly need two-five contacts attributed to therapeutic problems, their attitude towards medicines and their experiences of using them in daily life.…”
Section: Discussionmentioning
confidence: 99%